Family Assistance in Prevention of Stunting with Islamic and Health Perspectives - Endang Wahyuningsih; Syahbana Daulay (Urecol Journal. Part F: Community Development, 2021)
The incidence of short toddlers or commonly called stunting is one of the nutritional problems experienced by toddlers in the world today. Stunting at the age of toddlers is one of the obstacles that have a significant impact on growth and development. The effects of stunting are mostly irreversible and increase the incidence of repeated infections in 1000 HPK. The short-term impact of stunting is an increase in incidence, morbidity and mortality. Cognitive, motoric and verbal development in children is not optimal. The prevalence of stunting that occurs in Kalikebo Trucuk Klaten ranges from 10-14% of the total 490 toddlers, this is very worrying. This requires handling and cooperation of various sectors to reduce the incidence of stunting. With the large impact of stunting that affects toddlers as adults, it requires village governments, health workers and the role of educational institutions to move to prevent and reduce stunting rates in the community. This requires collaboration with various sectors of society. Our target for community service is mothers who have 9 stunting toddlers in Kalikebo Trucuk Village, Klaten. Service activities are carried out with the method of implementing family assistance in preventing stunting children in Kalikebo Village in the Covid-19 pandemic through education, lectures, demonstrations and discussions using leaflet print media. Which includes conducting assessment, planning and development planning and preparation related to activities, implementation and evaluation. The results of educational activities with lecture and demonstration models have a positive impact on knowledge, and stunting prevention efforts. Every child who is born has the right to his parents to receive care, maintenance, and care so that he grows up physically and psychologically healthy. Islam views children as a gift that is expensive and has a sacred status. This expensive gift is a trust that must be guarded and protected by parents in particular, because children are parents' assets and national assets.